COMPARISON OF THE EFFECTIVENESS OF CURCUMA DOMESTICA EXTRACT AND CURCUMA XANTHORRIZA EXTRACT AGAINST LIVER FUNCTION AND HEPATIC CELL INFLAMMATION ON STREPTOZOTOCIN-INDUCED DIABETES MELLITUS MICE - Amira Naufal; Alfin Ihza Trimahendra; Astika Widy Utomo; Vega Karlowee; Awal Prasetyo; Mochamad Ali Sobirin (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Diabetes mellitus can cause complications including liver damage, which has an impact on increasing levels of SGOT and SGPT in the blood, as well as inflamation and hepatic steatosis. Turmeric (Curcuma domestica) and java turmeric (Curcuma xanthorizza) are known to have high levels of curcumin and xanthorizzol as an antioxidant and proven to improve liver function. Antioxidant therapy in patients with NAFLD is known to improve liver function and histopathological features. The effects of turmeric and java turmeric extract on liver function in streptozotocin-induced diabetes mellitus mice are still unknown. Objective: Comparing effects of administered turmeric and java turmeric extract on liver function and histopathologic features of  streptozotocin-induced diabetes mellitus mice. Method: Research design Post Test Only Control Group Design are used. Male swiss mice around 25-30 gram are used. Streptozotocin-induced diabetes mellitus mice with a total samples (n = 20) divided into 4 groups, Control+PBS, Control+STZ, STZ+Turmeric, and STZ+Java Turmeric (an = 5). Blood glucose, weight, SGOT, SGPT levels and histopathologic features including percentage of inflamation and hepatic steatosis were examined at day 21. All the research data were analyzed using statistics program. Result: Turmeric and java turmeric extract cannot significantly reduce blood glucose level. Administration of java turmeric extract significantly reduce SGPT level against control+STZ group (84,12±17,53 vs. 36,3±27,4 u/L, p=0,018). Administration of turmeric extract significantly reduce hepatic cell inflamation against control+STZ group (30(26-68) vs. 20(15-30)%, p=0,035). Conclusion: Each turmeric and java turmeric extract can improve liver fuction and decreasing hepatic cell inflamation on streptozotocin-induced diabetes mellitus mice, but may not mediated by decreasing blood glucose level.